2016
DOI: 10.1002/ajhb.22901
|View full text |Cite
|
Sign up to set email alerts
|

Validity of body adiposity index in predicting body fat in Brazilians adults

Abstract: It was found that BAI does not replace other measurements of body fat, but compared with more complex methods can be an alternative for estimating the body fat in the absence of these methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
(65 reference statements)
2
23
0
1
Order By: Relevance
“…Emerging observational studies using BAI with overweight/obese adults yielded inconclusive results—with some criticizing the accuracy of BAI [15,16,17,18,19,20]. Thus, in light of these discrepancies (and given the high prevalence of excess adiposity in the Colombian population), in order to clarify the validity of BAI in predicting BF% among overweight and obese adults, we will conduct a cross-sectional study to evaluate the validity of BAI in a Latin American population.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging observational studies using BAI with overweight/obese adults yielded inconclusive results—with some criticizing the accuracy of BAI [15,16,17,18,19,20]. Thus, in light of these discrepancies (and given the high prevalence of excess adiposity in the Colombian population), in order to clarify the validity of BAI in predicting BF% among overweight and obese adults, we will conduct a cross-sectional study to evaluate the validity of BAI in a Latin American population.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, validation and accuracy studies carried out in Costa Rica [15] and Brazil [16] included 199 college students (mean age, 18.1 ± 2.6 years) and 706 healthy adults (mean age, 37.3 ± 12.1 years), respectively. The results showed that BAI is not recommended for BF% prediction among Latinos [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their high standard equivalents require expensive and special devices (Bergman et al 2011) they are vastly preferred by scientists to estimate the level of adiposity. A vast number of previous studies have documented the use of AIs in predicting the body adiposity evaluated via reference methods (Revicki and Israel 1986;Gallagher et al 1996;Taylor et al 2000;Neovius et al 2005;Ketel et al 2007;Völgyi et al 2008;Flegal et al 2009;Bergman et al 2011;Lambert et al 2012;Thomas et al 2013;Segheto et al 2017). Nonetheless, current literature presents limited evidence on the relation between these methods and other predictive techniques among different samples.…”
Section: Introductionmentioning
confidence: 88%
“…Caliper measured skinfold fat in three areas (arm, super iliac, and thigh). Then, the subcutaneous fat was calculated by the Jackson-Pollock body fat percent formula (24).…”
Section: Methodsmentioning
confidence: 99%